The effects Live High, Train Low/High at natural altitude on blood variables and endurance performance - Mirzaei, R. M. (New Approaches in Sport Science, 2020)
Purpose: The present study was done to specify the impacts of a protocol called "living high, training low and high (LHTLH)"on serum ET-1 and EPO levels as well as the 3000-m performance of endurance runners in Iran's national team. Method: eight male runners (aged 24.4±3.1, height of 180.5±4.2, weight of 66.7±3.4 and BMI of 20.1±5.0kg/m2) who cooperated voluntarily with regard to middle distance and marathon running (R2M system training) at high and low altitudes. All case studies did 3000-m test and blood samples were taken at a time period of 24-hours before and after the test. The intended tasks consisted of continuous, interval, aerobic and resistance exercises. The runners were to take part in 16 training sessions each week. It should be noted that the training lasted for 11 weeks according to (LHTLH) protocol. Variance with repeated measures (P=0.05) was utilized as the method to analyze the collected data. Results: It was shown that 3000-m time underwent significant decrease with regard to the time of impact both before and after the training. However, there were not significant changes in EPO (P=0.05). On the contrary the amount of ET-1 demonstrated significant increase (P=0.05). Conclusions: The results indicated that 3000-m time at lower altitudes will decrease on account of certain training programs. The reason is not directly related to the level of EPO. It is through hematological and metabolic changes as well as increase of ET-1 levels that performance under hypoxic and normoxic states happens to improve in the real sense.